Inhibition of oxygen-sensing prolyl hydroxylases increases lipid accumulation in human primary tubular epithelial cells without inducing ER stress - Schley, Gunnar (Cell Tissue Res, 2020)
The role of the hypoxia-inducible transcription factor (HIF) pathway in renal lipid metabolism is largely unknown. As HIF stabilizing prolyl hydroxylase (PHD) inhibitors are currently investigated in clinical trials for the treatment of renal anemia, we studied the effects of genetic deletion and pharmacological inhibition of PHDs on renal lipid metabolism in transgenic mice and human primary tubular epithelial cells (hPTEC). Tubular cell-specific deletion of HIF prolyl hydroxylase 2 (Phd2) increased the size of Oil Red-stained lipid droplets in mice. In hPTEC, the PHD inhibitors (PHDi) DMOG and ICA augmented lipid accumulation, which was visualized by Oil Red staining and assessed by microscopy and an infrared imaging system. PHDi-induced lipid accumulation required the exogenous availability of fatty acids and was observed in both proximal and distal hPTEC. PHDi treatment was not associated with structural features of cytotoxicity in contrast to treatment with the immunosuppressant cyclosporine A (CsA). PHDi and CsA differentially upregulated the expression of the lipid droplet-associated genes PLIN2, PLIN4 and HILPDA. Both PHDi and CsA activated AMP-activated protein kinase (AMPK) indicating the initiation of a metabolic stress response. However, only CsA triggered endoplasmic reticulum (ER) stress as determined by the increased mRNA expression of multiple ER stress markers but CsA-induced ER stress was not linked to lipid accumulation. Our data raise the possibility that PHD inhibition may protect tubular cells from toxic free fatty acids by trapping them as triacylglycerides in lipid droplets. This mechanism might contribute to the renoprotective effects of PHDi in experimental kidney diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00441-020-03186-w) contains supplementary material, which is available to authorized users.